Fluorinated quorum sensing inhibitors: enhancement of potency through conformational control. Issue 44 (28th October 2021) - Lizarme-Salas, Yuvixza; Yu, Tsz Tin; de Bruin-Dickason, Caspar; Kumar, Naresh; Hunter, Luke
Abstract : Stereoselective fluorination effectively pre-organises QS inhibitor molecules into the target-binding geometry, leading to higher potency. Abstract : The bacterial quorum sensing (QS) system is a target for non-lethal antibacterial agents that do not encourage the development of resistance. QS inhibitors commonly contain a polar "head" moiety and a lipidic "tail" moiety. In this work, we synthesised novel QS inhibitor candidates in which the lipidic "tail" is decorated with stereospecifically positioned fluorine atoms. The presence of fluorine is shown to bias the molecules into distinctive conformations that are pre-organised for binding to the QS receptor. This translates into significant increases in QS inhibitory potency.